(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
This research paper endeavors to describe as well as outline the mainly significant issues as well as the narrative consciousness of Aravind Adiga through the critical study of his debut novel The White Tiger. Adiga has exposed the bleakness of this country and has explored all the negative aspects of India. Through the novel he has made an attempt to pin point every problem which our post-colonial society is facing after independence. Though Balram was a brilliant student but due to poverty he was pulled out of school and has to work in a teashop, breaking coals and wiping tables in Dhanbad. In Dhanbad, in a quest to make his life better, he learns to drive and gets his break as a chauffeur for the son of a rich man from his village. The White Tiger is a dark comedy through which the author satirizes modern Indian caste system, social system, political system and economic system. Instead of showing India as a beautiful, mysterious, exotic and colorful land, Adiga has presented the realistic picture of contemporary Indian society with all its flaws and problems.